Estudos espectroscópicos e cromatográficos da proteína recombinante DevS do Mycobacterium tuberculosis - Lobão, Josiane Bezerra da Silva (2018)
DevS is a heme-based sensor protein directly involved in the dormancy process in Mycobacterium tuberculosis (Mtb). This phenomenons is associated to persistence of Mtb around the World. A better understanding of how this sensor works is key to the develop new therapeutic approaches. Here, recombinant DevS was expressed, purified and investigated by spectroscopic (UV-vis, fluorescence and CD) and chromatographic (gel filtration) techniques. Electronic spectroscopy was employed to evaluate the stability of the heme domain toward chemical denaturation. Guanidinium chloride was much more efficient than urea, whereas oxy-DevS (FeII-O2), an inactive form, was also more stable than carboxy-DevS(FeII-CO), active form. That might be due to hydrogen bonding taking place with oxygen. Fluorescence studies showed tryptophans emission was sensitive tochenges from active to inactive state. Interestingly, bis-ANS, used as a fluorescent probe, showed a indirect response to divalent metals enabling measurement of dissociation constants for Mg2+, Ca2+, Mn2+ e Zn2+. These metals have key role in the histidine kinase activity, however, there was no change in their affinities either in active or inactive states suggesting their binding is not involved in signal transduction. Circular dichroism measurements for active, FeII deoxy, and inactive forms, FeII-O2, showed no changes in the secundary structures, found mainly as α helix. However, CD in the near-UV for oxy-DevS showed significative changes at the aromatic residues in support to tryptophan fluorescence data. Nonetheless, CD of the heme in the visible showed there is no change in the conformation of propionate and vinyl, in contrast to the analogous heme-based sensor FixL. Analytical gel filtration data showed DevS is found as a mixture of octamer, tetramer and dimers, which was not reported before for any similar protein. Remarkably, all active forms of DevS favored octamers, while the inactive form to tetramers and dimers. This fast and reversible switch on the oligomerization states of DevS unraveled its mechanism of signal transduction, which might be employed also by other analogous systems.